The covalent radii derived from the first-principle data. (16th November 2020) - Nikolaienko, Tymofii Yu.; Chuiko, Valerii S.; Bulavin, Leonid A.
Abstract : We present a collection of covalent radii for the elements H, B, C, N, O, F, Si, P, S, Cl, Ge, As, Se, Br, derived from the recently introduced systematic non-empirical dataset of the covalent bond lengths built basing on 26, 050 molecular geometries and bond graphs obtained from quantum-chemical calculations using automated CLPO analysis with almost no input of empirical data. The obtained 'non-empirical' covalent radii, determined separately for single, double and triple bonds, have been found to be in good agreement with their empirical counterparts available in the literature. The distributions of deviations between the sum of proposed radii and the true bond lengths are analysed in details, with emphasis put on the role of the electron delocalisation on the bond lengths. Corrections to the additive covalent radii model due to the difference in the elements electronegativities are derived for Pauling electronegativity scale. We further assess the accuracy of distance-based discrimination between bonded and non-bonded pairs of atoms in which the interatomic threshold distance is parameterised via the found covalent radii. GRAPHICAL ABSTRACT: